1997
DOI: 10.1080/03610739708254033
|View full text |Cite
|
Sign up to set email alerts
|

Executive Control and the Comprehension of Medical Information by Elderly Retirees

Abstract: This study examined the independent contributions of executive control function, general cognition, age, education, and medication usage to the comprehension of medical information. Randomly selected elderly retirees (N = 105) more than 70 years of age completed the Executive Interview (EXIT25), the Mini-Mental State Exam (MMSE), and the Hopkins Competency Assessment Test (HCAT). Cognitive measures were stronger predictors of HCAT scores than age, education, or number of prescribed medications. A discriminant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 15 publications
0
40
0
2
Order By: Relevance
“…We assume that this decreasing efficiency is primarily mediated by declines in frontal lobe functioning, but the present data do not directly address the issue of the neurological locus of the effect. There is, however, other evidence suggesting that lower competence in performance of everyday tasks, such as comprehension of medical information, is associated with normative late-life changes in the brain, particularly the frontal lobes [27].…”
Section: Discussionmentioning
confidence: 96%
“…We assume that this decreasing efficiency is primarily mediated by declines in frontal lobe functioning, but the present data do not directly address the issue of the neurological locus of the effect. There is, however, other evidence suggesting that lower competence in performance of everyday tasks, such as comprehension of medical information, is associated with normative late-life changes in the brain, particularly the frontal lobes [27].…”
Section: Discussionmentioning
confidence: 96%
“…-Older adults evaluated in long-term-care settings have high rates, between 44% and 69%, of capacity impairment (Barton, Mallik, Orr, & Janofsky, 1996;Fitten & Waite, 1990;Krynski, Tymchuk, & Ouslander, 1994;Pruchno, Smyer, Rose, Hartman-Stein, & Laribee-Henderson, 1995;Royall, Cordes, & Polk, 1997;Tymchuk, Ouslander, & Fitten, 1988). Similarly, acutely hospitalized older patients have demonstrated transient capacity impairments (Carney, Neugroschl, Morrison, Marin, & Siu, 2001;Dellasega, Frank, & Smyer, 1996;Etchells et al, 1999;Fitten & Waite;Frank, Smyer, Grisso, & Applebaum, 1999).…”
Section: Impairment Within Patient Groupsmentioning
confidence: 99%
“…One study by Ruscin and Semla (1996) showed that, in a sample of elders with an average age of 80, 22% of those who were physically dependent and one third of those who had cognitive impairment were still responsible for taking their own medications. Compounding this situation, a study by Royall, Cordes, and Polk (1997) showed that half of residents in the community they studied had trouble comprehending medication information.…”
mentioning
confidence: 99%